Забутий кримський етнограф О. Олесницький - Непомнящий, А. (Народна творчість та етнографія, 2007)
The topic of the field and expedition work to the Crimean region in pre-Soviet times done by the scholars of the Moscow Lazarev Institute of the Eastern Languages is continuing to be understudied in the Ukrainian scholarship. This article is dedicated to the life and work of Olexiy Olesnytsky (1888-?), who actively worked on the problems of the Crimean Tatar ethnography. His student work “The Songs of Crimean Turks” (texts were collected on the southern side of the Crimea) attracted attention of the Prof. Hordlevsky, and the student received the medal and the recommendation to publish his book. In 1913 Olesnytsky published two versions of the song about the murder of the Orthodox priest by the Tatar. The work of this young scholar had an important scientific and cultural meaning and was unfairly forgotten.